1937
DOI: 10.1021/ja01288a004
|View full text |Cite
|
Sign up to set email alerts
|

The Compressibility of and an Equation of State for Gaseous Propane

Abstract: Substitution of the critical temperature (267.01°) and volume (0.416 liter per mole) into the equation gives a calculated pressure of 28.75 atm. The observed pressure is 27.00 atm.; and the error of extrapolation from 2 to 2.40 moles per liter is 6.5%. SummaryMeasurements are reported on the compressi-bility of liquid normal heptane over the temperature range from 30 to 250°and to 350 atmospheres, and on the compressibility of the gas phase from 275 to 350°and from a density of 1.0 to 5.0 moles per liter.The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

1955
1955
1973
1973

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 0 publications
0
16
0
1
Order By: Relevance
“…k-k* = y p ' ( 5 ) was utilized in conjunction with plots of the residual transport properties against density to develop correlations in which the reduced transport properties investigated for each substance were plotted against the reduced temperature for lines of constant reduced pressure. Although these reduced state correlations have proved to be of a high degree of accuracy, they are specific only to the substances investigated and can be extended to substances having similar critical compressibility factors and polarities only if reliable viscosity values are available for these substances for the establishment of their critical viscosities.…”
Section: (4)mentioning
confidence: 99%
“…k-k* = y p ' ( 5 ) was utilized in conjunction with plots of the residual transport properties against density to develop correlations in which the reduced transport properties investigated for each substance were plotted against the reduced temperature for lines of constant reduced pressure. Although these reduced state correlations have proved to be of a high degree of accuracy, they are specific only to the substances investigated and can be extended to substances having similar critical compressibility factors and polarities only if reliable viscosity values are available for these substances for the establishment of their critical viscosities.…”
Section: (4)mentioning
confidence: 99%
“…The early work of Dana et al (3) was followed by some additional calorimetric measurements of the latent heat of vaporization of this hydrocarbon (6). The volumetric behavior of the compound and the vapor pressure have been studied by several investigators (1,2,5,8,9). There existed discrepancies of the order of 5 B.t.u.…”
mentioning
confidence: 99%
“…For example, Reamer et al (1949) in comparing their data for propane with that of Beattie et al (1937) found an average deviation of 0.22% in the measured pressures for 50 data points. Similarly in comparing six data points for n-pentane, found an average deviation of 0.36% from the experimental resuIts of Sage and Lacey (1942).…”
Section: Discussionmentioning
confidence: 99%